TAFSIR VISUAL Kajian Resepsi atas Tafsir dan Ilustrasi dalam Tafsir Juz â€˜Amma for Kids - Zahroâ€™, Nafiatuz (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
rchange-newline"> Al-Qurâ€™an as hudan li al-nÄs and rahmatan li al-â€˜ÄlamÄ«n, can not be comprehended the mean without any exegesis. In order that Al-Qurâ€™an and Exegesis are always easy given in the life and proved its existence which shalih li kulli zaman wa makan, they era does not only consider social characterchange from the space and the time, but the subject too. It is consumer thatis containing of various ability standard and age. Unfortunately, almostall exegesis is product that presented as adult consumption; beside in thisfact the modernization demand each element of life to begin all aspect fromchildren age for the maturation and the success future. One of the worksfrom several works that has been established to fulfil the children neededis Tafsir Juz â€˜Amma for Kids with the new thing that most shown from thiswork is illustration. In this article, It uses reception method to fid listener reaction and AlQurâ€™an reader in the meaning explanation. Reception that is done bycommentator has succeeded to be concretized into exegesis text with simplelanguage; beside the reception that it is done by illustrator has succeededto be concretized into visual language that is illustration that in the fialaccompany in the gotten up of a functional relation between both of them.The existence of exegesis and illustration are cooperation and it is a formof integration-interconnection. Illustration which as functional before hasbecome a helper media, fially it has potential as independent to be anexegesis that is â€œVisual Exegesis.â€